The Social Interaction Ability of Early Age Children was Reviewed from The Lifestyle of Parents 'Hedonism - Hanum, Meidika Bana Klolida; Latiana, Lita (BELIA: Early Childhood Education Papers, 2020)
A lively lifestyle found in the modern era is the lifestyle of hedonism. Such a lifestyle is also among parents, seen from the high lifestyle of parents who follow the trend that is famous or booming as much as 71.875%, these parents have an idol or a reference in appearance and behavior. The purpose of this study is that parents pay more attention to their own behavior in order to provide the best examples for children, especially in the development of children's social interactions with their environment, so as to create a good personality in children. This research is a quantitative research type with research subjects of children aged 5-6 years as many as 120 children and is supported by the data of parents of children totaling 120 people in KB-TK HJ. Istriati Baiturahman 2 Semarang. Data collection techniques in this study are using a questionnaire with a scale of children's social interaction abilities, and the lifestyle scale of parental hedonism, while data analysis techniques use simple linear regression. The hypothesis of this study is that there is an influence of parental hedoniseme lifestyle on the social interaction abilities of children aged 5-6 years at KB-TK Hj. Istriati Baiturrahman 2 Semarang.The results of the study are based on statistical calculations, it can be concluded that there is a significant influence on the lifestyle of parental hedonism on children's negative social interaction abilities so that the hypothesis is accepted. The lifestyle of parental hedonism contributed 38.4% to the social interaction ability of children aged 5-6 years at KB-TK HJ. Istriati Baiturahman 2 Semarang.